2016
DOI: 10.3390/technologies4040033
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Corrosion Behavior of New Generation Ti-45Nb Porous Alloys Implant Devices

Abstract: Strategies to improve the mechanical compatibility of Ti-based materials for hard tissue implant applications are directed towards significant stiffness reduction by means of the adjustment of suitable β-phases and porous device architectures. In the present study, the effect of different compaction routes of the gas-atomized β-Ti-45Nb powder on the sample architecture, porosity, and on resulting mechanical properties in compression was investigated. Green powder compacted and sintered at 1000 • C had a porosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 42 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…Although the chemical stability of Ti-Nb alloys is high (because of their excellent passive layer behaviour [37]), an increase in pH, in acidification of the Ringer's solution from pH 7.5 to pH 0.5 resulted in negative corrosion potential shifts. The addition of NaCl further exacerbated the corrosion resistance [38][39][40][41][42].…”
Section: In Vitro Electrochemical Corrosion Testing Proceduresmentioning
confidence: 99%
“…Although the chemical stability of Ti-Nb alloys is high (because of their excellent passive layer behaviour [37]), an increase in pH, in acidification of the Ringer's solution from pH 7.5 to pH 0.5 resulted in negative corrosion potential shifts. The addition of NaCl further exacerbated the corrosion resistance [38][39][40][41][42].…”
Section: In Vitro Electrochemical Corrosion Testing Proceduresmentioning
confidence: 99%
“…Titanium-based implants in orthopedic surgery are often directly fixed in the host bone by press fit [ 21 , 22 , 23 , 24 ] or screw fixation [ 13 , 24 ]. Thereby, the highly diverging elastic properties of the implant material, e.g., cp-Ti or Ti-6Al-4V [ 25 ] and cortical bone [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], promote stress-shielding effects along the implant–bone interphase [ 35 , 36 ]. As a consequence, the osseointegration of the implant, especially bone ingrowth, may be affected [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the studies reported on in situ alloying of Ti and Nb with several content of niobium [ 57 , 59 ]. Prashanth et al [ 25 ] described the mechanical properties of a porous Ti-45Nb alloy manufactured by a classic sintering process and subsequent hot pressing. The aim of our present study was the mechanical and microstructural characterization as well as the determination of the printing parameters of the Ti-42Nb alloy that was applied in the SLM manufacturing process described for the first time.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical compatibility of an implant material usually requires specific values of strength, elastic modulus, tensile ductility as well as fatigue and wear properties [ 2 , 3 ]. The required mechanical properties can be achieved, for example, via alloy design [ 4 , 5 , 6 ], tailoring of complex microstructures [ 7 , 8 , 9 ], or synthesis of porous [ 10 , 11 ] and composite materials [ 12 , 13 ]. The biological compatibility of implant materials can be achieved through avoiding toxic elements and surface functionalization (e.g., surface coating or surface roughening) [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%